Crimean Tatars in the Soviet Ethnopolitics in the interwar twenty years. - Grigorii Kondratjuk (Крымское историческое обозрение)
The article studies formation of the Soviet Ethnopolitics of treatment of the Crimean Tatars in 1920–1930s. It analyses formation and realization of national policy in the Crimean ASSR towards the Crimean Tatars. The most important component of the Soviet Ethnicpolitics was the policy of “korenization of the apparatus”, creation of national village councils, implementation of agrarian reforms, formation of the proletariat from among the Crimean Tatars, reorganizations in cultural and humanitarian spheres.